Inside the gender Jihad: Women's reform in Islam - Wadud, Amina (Oneworld, 2006)
In her new book, Inside the Gender Jihad, Amina Wadud brings a wealth of experience from the trenches of the jihad to make a passionate argument for gender inclusiveness in the Muslim world. Knitting together scrupulous scholarship with lessons drawn from her own experiences as a woman, she explores the array of issues facing Muslim women today, including social status, education, sexuality, and leadership.
Keywords: cours; discipline; fem1000; femmes* musulmanes; genre; identités LGBTQIA2+; islam; philosophie; premier cycle; science des religions; sciences humaines; sexualité; thématiques

Debora et Judith : l’amour entre femmes dans l’église catholique. Et CIEL parlait, ce serait l’ENFER? - Bazinet, Colette (Recherches féministes, 2000)
Keywords: amériques; approches et analyses; compte-rendu; cours; discipline; fem1000; invisibilités; lesbianisme; premier cycle; québec; ressource en ligne; régions géographiques; science des religions; sciences humaines; sexualité; thématiques; église